A confocal-controlled Raman-LIBS hybrid microscope with high stability and spatial resolution. Issue 4 (17th March 2023) - Zhao, Weiqian; He, Chunjing; Li, Angze; Qiu, Lirong; Xu, Ke-Mi
Abstract : A novel confocal controlled Raman-LIBS hybrid microscope, with a high spatial resolution and antidrift property, has been developed. The microscope provides valuable compositional and structural analysis and is a powerful tool to study unknown minerals. Abstract : Probing elemental and molecular structural information with a high spatial resolution is a key bottleneck in determining unknown minerals in the fields of geology and space exploration. An untraditional confocal-controlled Raman-LIBS hybrid method with high spatial resolution and anti-drift properties has been developed to overcome this challenge. The method is the first to combine Rayleigh/reflected light, LIBS signal, and Raman spectrum to simultaneously measure geometrical topography and elemental and molecular structural information. The hybrid system utilizes real-time focus tracking the performance of Rayleigh/reflected light to achieve accurate spectral measurements. The axial-focusing resolution and lateral resolution for morphological imaging are improved to ∼15 nm and 600 nm, which improves the anti-drift capability and minimizes the laser ablation size, thereby achieving a high transverse resolution of ∼9 μm, and a high axial resolution of ∼10 μm. As a proof of concept, high-resolution topological and hybrid spectral maps of the Northwest Africa 13323 meteorite have been measured. The fusion of the LIBS and Raman data provides a detailed three-dimensional map of the elementary and compositional distributions of the meteorite. Further analysis of the D and G bands in the Raman map reveals structural information reflecting the thermal metamorphism of the meteorite. The proposed Raman-LIBS hybrid microscope provides valuable information for composition and structure analysis, and it is a powerful tool for studying unknown minerals in the fields of geology and space exploration.